Endovascular Treatment of Visceral Artery Aneurysms: Data Analysis of the DeGIR/DGNR Quality Management System - Weiss, Daniel; Jannusch, Kai; Wilms, Lena Marie; Peters, Helena Anne; Nadjiri, Jonathan; Antoch, Gerald; Ziayee, Farid; Minko, Peter (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2025)
Visceral artery aneurysms (VAA) are rare, and data on their occurrence and treatment are often outdated or heterogeneous. The objective of this study is to provide a comprehensive overview of features and interventional treatment options for VAA.We analyzed demographic, procedural, and clinical data on VAA from 2018 to 2022 based on data derived from the German Society for Interventional Radiology and Minimally Invasive Therapy (DeGIR) registry regarding demographic details, aneurysm characteristics, treatment processes, and outcomes such as technical success, complication rates, and radiation exposure. Group comparisons between aneurysm locations and types were calculated as dependent variables as well as occurrence of incomplete embolization, complication rates, technical success, duration of intervention, and dose-area-product (DAP).In total 647 patients were enrolled. The mean age was 66 years, with 68.5% male. The most affected arteries were splenic (27.5%) and renal (21.3%). True aneurysms were most common (56.7%). Technical success was 91.2%, while primary incomplete embolization occurred in 47.3%. Complications were observed in 4.8%, with a 0.2% mortality. Mean intervention duration was 67 min, mean fluoroscopic time was 36 min and mean DAP was 9560 cGycm2. There were no significant differences in primary incomplete embolization, complication rate, correct placement of embolization material, duration, and DAP based on aneurysm location. Aneurysm types showed a significant difference in incomplete embolization, with dissections having the highest rates and longest durations of intervention and highest DAP.The analysis of DeGIR quality management data reveals consistently high technical success and low complication rates in endovascular treatment of VAA. Dissecting aneurysms exhibit the highest rates in incomplete embolization, requiring the longest interventions and increased radiation. Enhancing the DeGIR registry with follow-up features would benefit assessing VAA occlusion rates. The data provide a comprehensive nationwide overview of how interventional radiology can impact treatment strategy.
Keywords: DeGIR registry data; module b; aneurysm; endovascular treatment; stent; coil